La animación y recreación y su incidencia en el fortalecimiento de la identidad cultural en los niños y niñas de 3 a 4 años de edad en la provincia de Cotopaxi cantón Latacunga parroquia Guaytacama en el CIVB “Nuevos Horizontes” en el periódo 2014-2015 - Llano Samache, Rosa Silvana (2015)
This research is focused on cultural identity strengthening in "New Horizonts" CIVB children of Latacunga Canton, Guytacama Parish because there is an institution problem, the lacking of an entertainment and recreational a manual facilities, and serve as a teaching tool to guide educators so in order to improve teaching and learning processes and thus improve the level of students’ knowledge and likewise the institution. After doing this research and obtained results through the various tools implementation that helped the information collection applied to principal, educators and parents, this research is very essential because it help to young children to develop their skills and above all to expand their knowledge, equally help the educators to possess a teaching tool in order to improve their social, intellectual, personal and academic development, managing to have a good academic performance life as professionals achieving change and develop a prosperous and quality society.